Supportive care needs among Indigenous cancer patients in Queensland, Australia: less comorbidity is associated with greater practical and cultural unmet need. (March 2016) - Diaz, A.; Bernardes, C.M.; Garvey, G.; Valery, P.C.
Abstract : Little is known about the supportive care needs (SCN) of Australian Indigenous cancer patients. This cross‐sectional study investigated the association between comorbidity and SCN among newly diagnosed Indigenous cancer patients in Queensland. Comorbidity was ascertained from medical chart review using the Charlson Comorbidity Index (CCI) and SCN were measured using the Supportive Care Needs Assessment Tool for Indigenous Peoples (SCNAT‐IP). Of 183 participants, 76 (42%) had no comorbidity (CCI = 0), 60 (33%) had had a CCI score of 1 and 47 (26%) had a CCI of two or more, with the most common condition being diabetes (30%). The most common moderate–high unmet need items varied between comorbidity groups, although all patients most frequently reported moderate–high unmet need in the Physical and Psychological and the Practical and Cultural needs domains. Patients with the greatest comorbidity (CCI ≥ 2) had significantly more reduced odds of practical and cultural needs than patients without comorbidity (OR 0.28, 95% CI 0.11–0.75). This appeared to be partially explained by time since diagnosis, age, whether they were receiving current treatment and residential remoteness. Patients' experience of chronic disease, hospitals and the healthcare system may better prepare them for the practical and cultural aspects of their cancer journey.